(untitled) (Experimental biology, 2021)
The article presents hydrochemical and ichthyological data on the study of Lake Solontsy in the North Kazakhstan region. Lake Solontsy is a shallow reservoir of local fisheries significance with a mirror area of 236 hectares. According to the hydrochemical regime, the lake is slightly alkaline, with water mineralization of 1.32 g/l. The ichthyofauna of the reservoir is represented by three species of fish, these are silver crucian carp, golden crucian carp, and firebrand rotan. The purpose of ichthyological selection is to collect data on the species composition, population structure, size and age composition, sexual structure, and other biological morphometric indicators of background fish. The dominant species in Solontsy Lake is the silver carp -84.4% of the total catch. The catch per effort of silver carp in research nets ranged from 0.2 to 15 kg/net (average 5.23 kg/net). The silver carp Carassius gibelio is represented by individuals from 2 to 7 years old. The catches of silver carp were dominated by individuals at the age of 5 years. The golden crucian carp Carassius carassius is represented by individuals from 3 to 5 years old, the sex ratio was 1:3 with a predominance of females. A complete morphometric analysis of silver and gold carp was carried out according to generally accepted ichthyological methods, the results of which allow us to say that there are no hybrid forms of carp in the Solontsy lake.